2010
DOI: 10.1039/b923938c
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the adsorption state and desorption kinetics of NO2 over Fe–zeolite catalyst by FT-IR and temperature-programmed desorption

Abstract: States of NO(2) adsorption and kinetics of NO(2) desorption over a Fe-loaded ZSM-5 type zeolite were investigated using Fourier transform infrared (FT-IR) spectroscopy and temperature-programmed desorption (TPD). The FT-IR spectra in NO(2)/N(2) flows showed that several adsorption species (NO(2), nitrite, nitrate, and NO(+)) existed; except for NO(2), these were considered to be formed via NO(2) dimerization and disproportionation reactions. The TPD spectra showed two distinct peaks, a low-temperature (LT) pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 63 publications
0
21
0
Order By: Relevance
“…The intensity of the octahedral aluminum peak at 0 ppm was also decreased in the spectra of the aged samples. These results indicate that the aluminum removed from the tetrahedral zeolite framework was converted into distorted "NMR invisible" Al species [10,24] aluminum peak in aged Fe-HZ more significantly was reduced than that of aged Fe-NaZ. The integrated peak area of the tetrahedral Al 3+ ions in the aged samples was around 53% in Fe-NaZ and 26% in Fe-HZ.…”
Section: Xrd and Nmr Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…The intensity of the octahedral aluminum peak at 0 ppm was also decreased in the spectra of the aged samples. These results indicate that the aluminum removed from the tetrahedral zeolite framework was converted into distorted "NMR invisible" Al species [10,24] aluminum peak in aged Fe-HZ more significantly was reduced than that of aged Fe-NaZ. The integrated peak area of the tetrahedral Al 3+ ions in the aged samples was around 53% in Fe-NaZ and 26% in Fe-HZ.…”
Section: Xrd and Nmr Resultsmentioning
confidence: 58%
“…5. The fresh Fe-ZSM-5 samples showed a strong signal at around 55 ppm, attributed to tetrahedrally coordinated aluminum, and a weak signal at around 0 ppm, assignable to octahedrally-coordinated aluminum (extra-framework) [10,24,25]. After hydrothermal aging, the intensity of the peak at 55 ppm was decreased owing to the removal of the aluminum from the tetrahedral zeolite framework.…”
Section: Xrd and Nmr Resultsmentioning
confidence: 98%
“…The phenomenon could be a combination of first adsorption of NO 2 and H 2 O to the surface of the carbon steel, formation of thin water film, and then absorption of NO 2 in this surface water film. There are many studies about the adsorption and surface reaction processes of NO 2 on solid surfaces in air, but the number of studies on iron is limited, [35][36][37] and no studies has been found for dense phase CO 2 . Details about the reactions between the steel substrate, water film and NO 2 is not known in dense phase CO 2 , but adsorption directly on the steel substrate cannot be ruled out.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…The strong band around 3675 cm −1 is associated with the Si-OH bond asymmetric stretching vibrations, and that around 1016 cm −1 is the Si–O stretching vibrations, and the peaks (around 3675 cm −1 and 1016 cm −1 ) of the composite PU/RE nanofiber gradually increased by increasing the amount of RE powder in the PU fiber. In addition, the band at 1072 cm −1 represents the C–O–C vibration [39,40]. The changes were apparent by increasing the amount of RE powder in the PU fiber, which indicates that the addition of the RE powder affected the C–O–C vibration in the PU fiber, showing a weak interaction between the molecules in the RE powder and the PU.…”
Section: Resultsmentioning
confidence: 99%